PARP inhibition in atherosclerosis and its effects on dendritic cells, T cells and auto-antibody levels - Erbel, Christian; Achenbach, Jessica; Akhavanpoor, Mohammadreza; Dengler, TJ; Lasitschka, Felix; Gleißner, Christian A.; Bea, F.; Katus, Hugo; Szabó, Gábor (European journal of medical research, 2011)
Atherosclerosis is a chronic inflammatory process. Poly(ADP-ribose) polymerase-1 (PARP), a nuclear enzyme linked to DNA repair, has been shown to be involved in atherogenesis; however, the effects on dendritic cells, T cells and serum auto-antibody levels are not fully understood.
Gesehen am 29.04.2022